"Fallen through the cracks": Teachers' perceptions of barriers faced by struggling literacy learners in secondary school. (1st October 2020) - Merga, Margaret K.
ABSTRACT: Struggling literacy learners are typically low achievers with poor engagement in literacy learning, and the gap between struggling and capable students widens as children move through the years of schooling. Literacy research and interventions for struggling literacy learners typically focus on the primary school years. The 2019 Supporting Struggling Secondary Literacy Learners mixed-methods project collected qualitative data on teacher perceptions of the barriers experienced by their struggling literacy learners in Australian mainstream secondary English classrooms. Recurring barriers included literacy skill gaps and English as an additional language status, absenteeism, home factors, student attitudes and engagement, school and systems factors, and learning difficulties and disabilities influencing learning. This project found high agreement with diverse individual and group level barriers, and diverse learner barriers were negatively associated with perceived adequacy of time to meet the needs of struggling literacy learners.